Inflammatory markers in palatine tonsils of children with obstructive sleep apnea syndrome - Chen,Vitor Guo (2020)
Abstract Introduction Obstrutive sleep apnea syndrome is characterized by repeated episodes of upper airway obstruction, associated with intermittent hypoxia and hypercapnia, and the main risk factor in childhood is adenotonsillar hypertrophy. The lymphocytes in these structures are responsible for local and systemic immune responses. Objective Verify the levels of the inflammatory markers, IL-1β, IL-4, IL-6, IL-8, IL-10, IL-15, TNF-α, CRP and α1-GP, in the tonsils of children with and without obstructive sleep apnea syndrome. Methods This cross-sectional prospective study included 34 children with complains of snoring, difficulty breathing during sleep or recurrent tonsillitis. Patients underwent to a complete otorhinolaryngological examination, nasal endoscopy and polysomnography and were divided into two groups with 17 children each: obstructive sleep apnea syndrome group and control group. All underwent an adenotonsillectomy. Cytokines were measured in the collected tonsils (ELISA and Multiplex methods). Results Statistically significant increasing were observed between IL-8 and IL-10 cytokines of patients with obstructive sleep apnea when compared to the control group; also between c-reactive protein and α1-GP of the tonsils cortical region in children with obstructive sleep apnea syndrome when compared with the medullary region. There were no statistically significant differences for the remaining inflammatory mediators. Conclusion After the analysis of the levels of pro and anti-inflammatory markers (IL-1β, IL-4, IL-6, IL-8, IL-10, Il-15, TNF-α, CRP, α1-GP) in the tonsils, we observed higher levels of markers IL-8 and IL-10 in pediatric patients with obstructive sleep apnea syndrome.